2015
DOI: 10.3310/hta19620
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Thessaly test, standardised clinical history and other clinical examination tests (Apley’s, McMurray’s and joint line tenderness) for meniscal tears in comparison with magnetic resonance imaging diagnosis

Abstract: BackgroundReliable non-invasive diagnosis of meniscal tears is difficult. Magnetic resonance imaging (MRI) is often used but is expensive and incidental findings are problematic. There are a number of physical examination tests for the diagnosis of meniscal tears that are simple, cheap and non-invasive.ObjectivesTo determine the diagnostic accuracy of the Thessaly test and to determine if the Thessaly test (alone or in combination with other physical tests) can obviate the need for further investigation by MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…We will review the pertinent anatomy, biomechanical function of ligamentous structures, mechanisms of injury, and the imaging appearances of specific ligamentous and meniscal injuries in the preoperative setting. Data regarding clinical evaluation of meniscal and ligamentous injuries are highlighted in the Table (2)(3)(4)(5). The role of imaging in the treatment decision-making process will also be discussed where relevant.…”
mentioning
confidence: 99%
“…We will review the pertinent anatomy, biomechanical function of ligamentous structures, mechanisms of injury, and the imaging appearances of specific ligamentous and meniscal injuries in the preoperative setting. Data regarding clinical evaluation of meniscal and ligamentous injuries are highlighted in the Table (2)(3)(4)(5). The role of imaging in the treatment decision-making process will also be discussed where relevant.…”
mentioning
confidence: 99%
“…The medial joint line tenderness test was the only physical test in our diagnostic cluster for traumatic SMT. Previous findings showed that this test was not diagnostically valid when individually performed [16,19,49]. Interestingly, the test, when combined into a diagnostic cluster with patient's history elements, yields adequate diagnostic accuracy but only for traumatic SMT.…”
Section: Discussionmentioning
confidence: 90%
“…Also, mechanical symptoms, when present, do not arise exclusively from meniscal tears and may be positive in other disorders such as ACL tear or osteoarthritis [3,6]. This adds to the growing evidence suggesting that these history elements and tests may have limited diagnostic value, as well as a possibly limited use as a surgical criterion [3,10,16,18‐20,22,23,49,52‐55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Thessaly test, Mcmurray's test, and Apley's test may be positive, and joint line tenderness may be present. However, these tests have limited diagnostic accuracy [13], and further investigations are often required, such as magnetic resonance imaging (MRI) studies.…”
Section: Discussionmentioning
confidence: 99%